Requalification of Social Housing: Ingote plateau (Coimbra). Issue 2 (December 2020) - Virtudes, Ana; Nascimento, Ana; García, Irene Mendoza; Fonseca, António
Abstract: Social housing neighbourhoods are issues for several approaches and studies in all domains, the architectural scope and the urban scale. There are several examples of academic research focused on this topic. However, there is still much ink to spill regarding the scientific interest of peripheries, such as in the case of Ingote plateau, a suburb at the Portuguese city of Coimbra. This suburb is the result of three housing developments from different periods of time, according to the national policy to provide social houses: the Ingote (1970s), the António Sérgio (1980s), and the Rosa (1990s) suburbs. These residential areas are associated with the problems related to the suburban social housing, such as scarcity of social and economic means or shortage of urban conditions. Social housing suburbs are complex entities and their rapid growth has contributed to change the spatial identity of cities, leaving room for new questions about the concept of neighbourhood and its role at the urban scale. As this article aims to show, the geographical location of Ingote plateau makes it a target of territorial and social exclusions. Therefore, an urban design solution was proposed in order to rethink this area, developing strategies for its integration in the urban fabric. As the main conclusion, the project maintains the number of dwellings, improving the quality of public spaces, facilities, greenery and leisure to serve not only the local community but also the city as a whole. The main goal was to reinforce the identity, promoting the safety of locals, making them proud of their suburb.